Hierarchical Relations and Popular Protest: Anti-Constitutional opposition in the Spanish Basque Country (Biscay, 1820-1825) - Pablos Ormaza, Ane Miren; Artola Renedo, Andoni (Hispania Nova, 2022)
This paper addresses the specific features of the anticonstitutional opposition in Biscay (Spain) prior to the First Carlist War. Scholars’ interest in the latter conflict has somehow distorted the interpretation of earlier royalism, which –in a clear teleological reading- has been seen as a mere precedent of the great carlist counter-revolution that was to come. As a result, historians have often attributed to the plebeian sectors reactionary and/or counter-revolutionary ideological categories that were alien to their context, for they only appeared later. In order to avoid this teleological bias, our work makes extensive use of abundant archival sources that reveal the complexity of the popular classes’ role in the early antiliberal opposition. We aim to show that plebeian actions cannot be reduced to a royalist or counterrevolutionary militancy, but must rather be understood within the social and cultural framework of the Ancien Régime and its repertoires of mobilization.